Apoptotic Effects Sulfated Polysaccharides of Caulerpa racemosa Extract on Colorectal Cancer Cells through Caspase-3 - Wijaya, Taswin; Akmal, Andi Aida Munirah; Herman, Nabilah; Hasan, Aisyah Amaliah; Hafiz, Arya; Widyastuti, Helmy (Cell and BioPharmaceutical Institute, 2025)
AbstractBackground: Colorectal cancer originates from progressive genetic alterations in colorectal epithelial cells. While current therapies (surgery, radiotherapy, and chemotherapy) remain cornerstone treatments, chemotherapy often induces systemic toxicity, adverse effects, and acquired resistance. Sulfated polysaccharides (SPs) from the green alga Caulerpa racemosa demonstrate higher sulfate content than red algal derivatives, correlating with enhanced bioactivity. Despite their potential, SPs from green algae remain understudied compared to brown and red algal counterparts. This study evaluated the anticancer potential of C. racemosa SPs against colorectal cancer through viability inhibition and apoptosis induction.Materials and Methods: SPs were extracted via Microwave-Assisted Extraction (MAE) and characterized using iodine testing and FTIR spectroscopy. Cytotoxicity was evaluated in WiDr colorectal cancer cells using MTT assay after 24-hour exposure. Apoptotic mechanisms were investigated through in silico molecular docking targeting Caspase-3 activation.Results: SPs were confirmed by a blue color change and FTIR absorption at 1232 cm-1. At 100 µg/mL, low toxicity was observed based on abundant formazan crystals. Concentrations of 200–400 µg/mL showed predominant viable cells, whereas 500 µg/mL caused significant growth inhibition and cell death. In silico analysis demonstrated that SPs may induce apoptosis by Caspase-3 activation.Conclusion: SPs of C. racemosa inhibit colorectal cancer cell viability at a concentration of 500 µg/mL and may induce apoptosis via Caspase-3 activation.Keywords: apoptosis, Caulerpa racemosa, colorectal cancer, sulfated polysaccharides